Phytoconstituents and Antioxidant Profiling of Avicennia marina (Forsk.) Vierh. Heartwood Extract Sourced from Bagan Kuala: A Novel Natural Source for Radical Scavenging Applications - Julia Reveny; Firdha Sekar Rahayu; Yuandani (Talenta Publisher, 2026)
Avicennia marina (Forssk.) Vierh., commonly known as 'api-api' or white mangroves, are woody shrubs and tropical plants that inhabit mangrove ecosystems, which occur at the interface between terrestrial and marine environments. Salinity is a critical environmental factor in mangrove habitats. Plants growing in such extreme conditions exhibit elevated concentrations of specific antioxidant compounds. Various parts of plants, including heartwood, are known to contain an abundance of extractive components compared to sapwood. Objective: This study was the first to evaluate the antioxidant activity of A. marina heartwood extract. Method: The applied method of sample extraction comprises ethanol-based maceration, qualitative phytochemical analysis based on observable visual changes, and the assessment of antioxidant activity employing the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay using UV-Vis Spectrophotometry. Result: heartwood extract of Avicennia marina exhibits phytochemical constituents that comprise alkaloids, tannins, saponins, triterpenoids, and flavonoids. The antioxidant capacity of the extract showed strong antioxidant activity with an IC50 value of 61.50 µg/mL (R2 = 0,9962). Conclusion: The current study confirms the promising antioxidant activities of Avicennia marina heartwood sourced from Bagan Kuala. These marine biological resources can be explored further as an ailment for degenerative disease induced by Reactive Oxidative Stress (ROS), which can be made into an oral supplement or topical preparations, thus generating a greater economic value.